Literature Review on Aadhar Based Secure Biometric Voting Machine - Prajapati, HN; Kshirsagar, SK; Patil, VB; Vitore, SG (International Journal of Computer Sciences and Engineering, 2025)
In Democratic countries like India, Bangladesh the voting system plays a major role during elections. Traditionally, the election commission in India uses electronic voting machines which need more manpower, time-consuming and also they are less trusted. For avoiding misconceptions during elections, there are lot of advanced techniques are being proposed using various methods. The voting system is managed in a easier way as all the users should login by Aadhar card number and password and click on his favorable candidates to cast the vote. In this paper we will review on Aadhar Based Biometric Voting Machine Survey, the research conducted by various researchers related to the discipline of biometric voting machine are taken into consideration and discussed in chronological order. With the help of this literature survey, it has tried to find out the basic of biometric voting system, improvement of various methods for biometric voting system, and classification of various newly developed methods.